Participatory Communication and Digital Strategies in Environmental Advocacy: A Narrative Review of Frameworks and Impacts - Sumarni Zainuddin; Muliawan, Dadang; Trihandayani, Indah; Mambang (Yayasan Sinergi Kawula Muda, 2024)
Effective communication strategies have become indispensable in environmental advocacy amid escalating ecological crises.This narrative review explores how participatory and digital communication frameworks influence environmental awareness, public engagement, and policy transformation across varied sociopolitical contexts.Drawing on empirical literature from 2010 to 2024, sources were identified through Scopus, Google Scholar, and PubMed using terms like